2021
DOI: 10.1186/s12885-021-08506-z
|View full text |Cite
|
Sign up to set email alerts
|

miR-29a-3p inhibits endometrial cancer cell proliferation, migration and invasion by targeting VEGFA/CD C42/PAK1

Abstract: Background This study aimed to investigate the mechanism of miR-29a-3p in regulating endometrial cancer (EC) progression. Methods A total of 72 EC patients were enrolled. EC cells were transfected. Cells proliferation, cloning ability, migration and invasion were researched by MTT assay, colony formation experiment, cell scratch test and Transwell experiment respectively. Dual-luciferase reporter assay was performed. Xenograft experiment was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…The VEGF family consists of cytokines known to be angiogenic factors that participate in blood vessel formation and lymphangiogenesis (30). VEGFA is the main member of this family of proteins, which has been revealed to regulate cell proliferation, apoptosis and invasion (11)(12)(13)31,32). In particular, VEGFC has also been reported to impact the progression of hemangioma (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The VEGF family consists of cytokines known to be angiogenic factors that participate in blood vessel formation and lymphangiogenesis (30). VEGFA is the main member of this family of proteins, which has been revealed to regulate cell proliferation, apoptosis and invasion (11)(12)(13)31,32). In particular, VEGFC has also been reported to impact the progression of hemangioma (22).…”
Section: Discussionmentioning
confidence: 99%
“…Vascular epithelial growth factor A (VEGFA) is a critical regulator of a number of cellular processes, including proliferation, apoptosis and invasion (11)(12)(13). Notably, it has been demonstrated that VEGFA can serve a role in the pathogenesis of hemangioma in several ways, including through the promotion of angiogenesis (14).…”
Section: Introductionmentioning
confidence: 99%
“…30 Geng et al reported that miR-29a-3p inhibited the proliferation, migration, and invasion of endometrial cancer cells by targeting VEGFA/CDC42/PAK1. 31 In addition, it has also been concluded that miR-29a-3p could inhibit the migration ability and proliferation of cervical cancer cells by directly targeting SNIP1. 32 Based on lncRNA HOXA-AS3 interacting with miR-29a-3p, the molecular mechanism of cervical cancer was deeply explored in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that aberrant expression of miR-29a-3p is involved in the development of many diseases. For example, in endometrial cancer, miR-29a-3p inhibits cell proliferation, migration and invasion by targeting VEGFA/CDC42/PAK1 signaling pathway ( 13 ). MiR-29a-3p suppressed the migration and proliferation of HeLa cells by directly targeting SNIP1 ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-29a-3p, reporte-dly, is a pivotal regulator in cancer biology. Specifically, miR-29a-3p dysregulation takes part in the progression of certain cancers, such as osteosarcoma ( 11 ), breast cancer ( 12 ), endometrial cancer ( 13 ), hepatocellular carcinoma ( 14 ). Instead, the role of miR-29a-3p in ONFH and SAON is unknown.…”
Section: Introductionmentioning
confidence: 99%